2014
DOI: 10.1159/000369455
|View full text |Cite
|
Sign up to set email alerts
|

New Strategies and Concepts in Organ Preservation

Abstract: Organ transplantation is still affected by a notable degree of preservation-associated ischemia and reperfusion injury, which can seriously hamper early graft function. The increasing extension of the criteria for donor organ acceptance, especially for organs that have suffered from periods of warm ischemic injury prior to graft retrieval, results in even higher demands on preserving these ischemia-sensitive grafts. Growing attention is thus directed towards more dynamic preservation methods instead of simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 74 publications
0
30
0
Order By: Relevance
“…It has been shown that VSOP represents the best method of fully oxygenating an entire human-sized organ when compared with CS, MP, and OMP [11,29,30,31]. Also compared to other techniques, VSOP is a relatively inexpensive and simple technique, with favorable reported results [8,11,32,33,34]. Some drawbacks of VSOP, however, are the potential formation of gaseous emboli and the low potential for waste removal and nutrient supply when compared to MP and OMP [11,35].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that VSOP represents the best method of fully oxygenating an entire human-sized organ when compared with CS, MP, and OMP [11,29,30,31]. Also compared to other techniques, VSOP is a relatively inexpensive and simple technique, with favorable reported results [8,11,32,33,34]. Some drawbacks of VSOP, however, are the potential formation of gaseous emboli and the low potential for waste removal and nutrient supply when compared to MP and OMP [11,35].…”
Section: Discussionmentioning
confidence: 99%
“…In order to increase the use of less optimal organs for transplantation, aerobic extracorporeal normothermic, subnormothermic, and hypothermic preservation techniques have been developed which demonstrate an improved preservation quality compared to anaerobic preservation for kidney, liver, heart, lung, and pancreas grafts [8,9,10,11,12,13]. The benefit from aerobic preservation has been related to the fact that even at hypothermia, a residual metabolism is operative which has restorative capacities if oxygen is provided [8,14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations